2018
DOI: 10.1038/s41598-018-26976-3
|View full text |Cite
|
Sign up to set email alerts
|

DNA Barcoding of Freshwater Fishes of Indo-Myanmar Biodiversity Hotspot

Abstract: To develop an effective conservation and management strategy, it is required to assess the biodiversity status of an ecosystem, especially when we deal with Indo-Myanmar biodiversity hotspot. Importance of this reaches to an entirely different level as the hotspot represents the area of high endemism which is under continuous threat. Therefore, the need of the present study was conceptualized, dealing with molecular assessment of the fish fauna of Indo-Myanmar region, which covers the Indian states namely, Man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 69 publications
2
22
1
Order By: Relevance
“…Nudibranch molluscs are marine invertebrates that display unique adaptations, like the storage of stinging nematocysts from cnidarian prey in their specialized dorsal outgrowths, i.e., cerata, for defence (Martin et al, 2009). Cold waters are commonly equated with low species richness and diversity, whereas tropical waters are usually noted as biodiversity hotspots for marine animals (e.g., Roberts et al, 2002;Hoeksema, 2007;Barman et al, 2018). It has been concluded that a rise in sea water temperature along a latitudinal gradient from the poles to the equator considerably increases biodiversity (e.g., Bickford et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Nudibranch molluscs are marine invertebrates that display unique adaptations, like the storage of stinging nematocysts from cnidarian prey in their specialized dorsal outgrowths, i.e., cerata, for defence (Martin et al, 2009). Cold waters are commonly equated with low species richness and diversity, whereas tropical waters are usually noted as biodiversity hotspots for marine animals (e.g., Roberts et al, 2002;Hoeksema, 2007;Barman et al, 2018). It has been concluded that a rise in sea water temperature along a latitudinal gradient from the poles to the equator considerably increases biodiversity (e.g., Bickford et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…DNA barcoding has been applied to numerous vertebrate (e.g., Hebert et al, 2004; Álvarez-Castañeda et al, 2011; Mendoza et al, 2016; Ramirez et al, 2017; Barman et al, 2018) and invertebrate (e.g., Barrett and Hebert, 2005; Moura et al, 2011; Barco et al, 2016; Jin et al, 2018) taxa, but the barcoding of herpetofauna largely has lagged behind. The initiation of the “ColdCode” campaign (Murphy et al, 2013) has led to a more concentrated effort to provide reference libraries for reptiles and amphibians, including those focused on specific taxa (e.g., Dang et al, 2015; Liu et al, 2015) and broad-scale regional assessments (e.g., Nagy et al, 2012; Guarnizo et al, 2015; Hawlitscheck et al, 2016; Vasconcelos et al, 2016; Deichmann et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Further, the large-scale attempt has been accomplished in recent past to generate the barcode data of 109 freshwater fishes from Indo-Myanmar biodiversity hotspot; considering Barak, Brahmaputra, Chindwin, and Karnafuli Rivers (Barman et al. 2018 ). However, the publicly available barcode data of freshwater fishes are still inadequate from each drainage system.…”
Section: Introductionmentioning
confidence: 99%